Computational justification of experiments on irradiation of lithium ceramics in the WWR-K reactor - Shaimerdenov, A.A.; Akhanov, A.M.; Sairanbayev, D.S.; Aitkulov, M.T.; Kisselyov, K.S.; Bugybay, Zh.T.; Merezhko, M.S.; Mukhamejanova, A.T. (Recent Contributions to Physics, 2022)
The results of neutron-physical and thermophysical calculations of different designs of capsules with lithium ceramics under irradiation in the WWR-K reactor are presented. The main conditions for irradiation of lithium ceramics in the WWR-K reactor core are described. Two types of reactor experiments with lithium ceramics have been shown to be possible: high-temperature irradiation with in-situ registration of tritium release and low-temperature irradiation with post-reactor experiments on sample degassing. When lithium ceramics are irradiated in the standard capsule, the temperature of the samples does not exceed 60°C, but when irradiated in the experimental device, the temperature of the samples can be raised to 800°C. The dependence of the temperature of the samples in the irradiation capsule of the experimental device on the reactor power is given. Estimates are given for the tritium yield in lithium ceramics (separately for 6Li(n,α)T and 7Li(n,αn)T nuclear reactions) for different neutron flux densities. The rate of tritium generation in the peripheral irradiation channel of the WWR-K will be 2 105 s-1. The reactivity effect from loading a sample capsule into the core of the WWR-K will be minus 0.05 βeff for the standard capsule and minus 0.3 βeff for the experimental device.